Perancangan dan Karakterisasi Antena Vivaldi untuk Aplikasi Anti-Drone Jammer pada Frekuensi 1,2 GHz, 2,4 GHz, dan 5,8 GHz - Muhammad Umar Zain; Fitri Elvira Ananda; Nanang Kurniawan (Spektral, 2026)
This study presents the design of three vivaldi antennas operating at 1.2 GHz, 2.4 GHz, and 5.8 GHz, which are implemented as part of an anti-drone jammer transmission system. Unmanned aerial vehicles (UAVs), commonly known as drones, have experienced rapid growth and are widely utilized in both military and civilian applications. This development has increased the demand for effective counter-drone technologies, one of which is an anti-drone jammer system designed to disrupt radio-frequency communication between drones and their controllers. The antenna design process includes planning, mathematical calculations, simulation, fabrication, and performance characterization. Measurement results show return loss values of −20.52 dB, −15.16 dB, and −34.16 dB at 1.2 GHz, 2.4 GHz, and 5.8 GHz, respectively, with corresponding VSWR values of 1.17, 1.38, and 1.04. The proposed antennas achieve gains of 5.28 dBi, 8.34 dBi, and 6.15 dBi at the respective operating frequencies. Radiation pattern measurements indicate directional characteristics in the vertical plane, making the antennas suitable for jamming applications. The results confirm that proper simulation and optimization processes play a crucial role in achieving antenna performance that satisfies design specifications and supports implementation in anti-drone jammer systems.